Risks of investment portfolio of bank institutions of Ukraine - Дєєва, Наталія Едуардівна (Technology audit and production reserves, 2015)
In the article an assessment of concentration of securities in the assets of depository corporations is provided, compliance with regulations investing in securities in the banking system of Ukraine to determine the existing reserves is investigated. The conclusion of low investment activity of banks on the one hand, and the great potential of securities transactions on the other are done. The study found that a group of banks of Ukraine by size are significantly different in scope and quality of portfolio securities, the overwhelming majority of securities is concentrated in banks in group I, the greatest risk of securities available for sale are banks of group II and group IV, held to maturity – banks of group IV. The obtained results are important given the fact that the NBU increased provisioning requirements for securities that are not listed and traded on the stock exchanges that encourage commercial banks to invest in financial instruments market. The result of the study was the development of anti-crisis measures in the stock market to stimulate the investment activity of depository corporations and will reduce its risks: further implementation of international financial reporting standards on accounting and disclosure of securities, transfer illiquid securities in balances of hospital banks for their further implementation by fair value in the post-crisis period.